2018
DOI: 10.6061/clinics/2018/e131
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral spatial neglect in the acute phase of ischemic stroke can predict long-term disability and functional capacity

Abstract: OBJECTIVE:The aim of this study was to assess the relationship between the degree of unilateral spatial neglect during the acute phase of stroke and long-term functional independence.METHODS:This was a prospective study of right ischemic stroke patients in which the independent variable was the degree of spatial neglect and the outcome that was measured was functional independence. The potential confounding factors included sex, age, stroke severity, topography of the lesion, risk factors, glycemia and the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…An unexpected finding was that neglect was observed more frequently in women, as previous studies found the incidence to be equal across genders when performing drawing tasks [31]. As previously reported, we confirm that neglect is associated with a more severe stroke [30,32] but the extent of this is very marked in our data, ranging from 4% of those with mild strokes through to 84% of those with severe strokes. We found that neglect was more common in individuals who were dependent before their admission, but co-morbidities such as diabetes and previous stroke/Transient Ischemic Attach (TIA) although present were curiously less frequent.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An unexpected finding was that neglect was observed more frequently in women, as previous studies found the incidence to be equal across genders when performing drawing tasks [31]. As previously reported, we confirm that neglect is associated with a more severe stroke [30,32] but the extent of this is very marked in our data, ranging from 4% of those with mild strokes through to 84% of those with severe strokes. We found that neglect was more common in individuals who were dependent before their admission, but co-morbidities such as diabetes and previous stroke/Transient Ischemic Attach (TIA) although present were curiously less frequent.…”
Section: Discussionsupporting
confidence: 90%
“…The assessment for neglect is conducted on arrival in the very acute phase of stroke. As impairments resolve quickly in the acute stage, it could be that some of these resolve [32]. The data are also subject to data entry error as quality control for a national database is not feasible.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Unilateral spatial neglect (USN) consists of an exaggerated spatial asymmetry in processing information in bodily and/or extrabodily space due to a cerebral lesion, which cannot be explained by primary motor or sensory deficits 1 . USN occurs in approximately 50% of individuals after right hemisphere stroke, and may persist in 75% of cases in the chronic phase, 2 leading to poor functional outcome 3 and low quality of life 4 . Some evidence suggests that top‐down and bottom‐up USN treatment can help effectively improve spatial attention and alleviate right‐hemisphere bias after stroke 5 .…”
mentioning
confidence: 99%
“…4 Moreover, USN has important clinical implications, as it leads to prolonged periods of hospitalization, impaired functional recovery, and worsening quality of life. 5,6…”
Section: Introductionmentioning
confidence: 99%